Legitimasi Status Kelompok Alawiyyin dalam Struktur Rabithah Alawiyah : Studi Antropologi Politik - Hamdi, Sy Sultan; Tang, Mahmud; Yahya, Yahya; Yusuf, Andi Muhammad; Idris, Usman (Universitas Cenderawasih, 2024)
The alawiyyin group or groups that claim to be descendants of the Prophet Muhammad SAW. have differences of opinion regarding the exclusivity of their status. Their status in the surrounding community has become a special privilege for their group. An organization that wants legitimacy for the alawiyyin group is trying to trace the descendants of the alawiyyin group to remote villages, starting in the 19th century. It makes the rabithah alawiyah organization or the unity of the alawiyyin group experience difficulties in legitimizing the alawiyyin groups in the area. This research analyzes the causes of exclusivity and legitimacy in the status legitimation process, especially between rabithah alawiyah and alawiyyin groups in rural areas. Ethnography is an appropriate method for analyzing and analyzing active observation data in this research. Some data and informants in in-depth interviews that had the nuance of friendly conversation because the researcher himself was an alawiyyin who could carry out in-depth analysis in this research. The results of this research found that most of the alawiyyin groups in rural areas did not want their status to be made public, was even an informant's grandfather who hid their written genealogy to avoid the arrogance that would occur to his children and grandchildren when they legitimized their status. As a finding from this research, rabithah alawiyah as an institution that legitimizes the status of alwiyyin groups nationally and internationally, digitalization of nasab needs to be digitalized, so that those in rural areas or alawiyyin groups in remote parts of Indonesia can register their nasab or clan at this institution Rabitha Alawiyah.